The Chromatin Regulator Ankrd11 Controls Palate and Cranial Bone Development - Roth, Daniela Marta; Baddam, Pranidhi; Lin, Haiming; Vidal-García, Marta; Aponte, Jose David; De Souza, Sarah-Thea; Godziuk, Devyn; Watson, Adrianne Eve Scovil; Footz, Tim; Schachter, Nathan F.; Egan, Sean E.; Hallgrímsson, Benedikt; et al. (Frontiers in Cell and Developmental Biology, 2021)
Epigenetic and chromatin regulation of craniofacial development remains poorly understood. Ankyrin Repeat Domain 11 (ANKRD11) is a chromatin regulator that has previously been shown to control neural stem cell fates via modulation of histone acetylation. ANKRD11 gene variants, or microdeletions of the 16q24.3 chromosomal region encompassing the ANKRD11 gene, cause KBG syndrome, a rare autosomal dominant congenital disorder with variable neurodevelopmental and craniofacial involvement. Craniofacial abnormalities include a distinct facial gestalt, delayed bone age, tooth abnormalities, delayed fontanelle closure, and frequently cleft or submucosal palate. Despite this, the dramatic phenotype and precise role of ANKRD11 in embryonic craniofacial development remain unexplored. Quantitative analysis of 3D images of KBG syndromic subjects shows an overall reduction in the size of the middle and lower face. Here, we report that mice with heterozygous deletion of Ankrd11 in neural crest cells (Ankrd11nchet) display a mild midfacial hypoplasia including reduced midfacial width and a persistent open fontanelle, both of which mirror KBG syndrome patient facial phenotypes. Mice with a homozygous Ankrd11 deletion in neural crest cells (Ankrd11ncko) die at birth. They show increased severity of several clinical manifestations described for KBG syndrome, such as cleft palate, retrognathia, midfacial hypoplasia, and reduced calvarial growth. At E14.5, Ankrd11 expression in the craniofacial complex is closely associated with developing bony structures, while expression at birth is markedly decreased. Conditional deletion of Ankrd11 leads to a reduction in ossification of midfacial bones, with several ossification centers failing to expand and/or fuse. Intramembranous bones show features of delayed maturation, with bone remodeling severely curtailed at birth. Palatal shelves remain hypoplastic at all developmental stages, with a local reduction in proliferation at E13.5. Our study identifies Ankrd11 as a critical regulator of intramembranous ossification and palate development and suggests that Ankrd11nchet and Ankrd11ncko mice may serve as pre-clinical models for KBG syndrome in humans.